An efficient first-order conditional gradient algorithm in data-driven sparse identification of nonlinear dynamics to solve sparse recovery problems under noise - Carderera, Alejandro; Pokutta, Sebastian; Schütte, Christof; Weiser, Martin (Journal of computational and applied mathematics, 2025)
Governing equations are essential to the study of nonlinear dynamics, often enabling the prediction of previously unseen behaviors as well as the inclusion into control strategies. The discovery of governing equations from data thus has the potential to transform data-rich fields where well-established dynamical models remain unknown. This work contributes to the recent trend in data-driven sparse identification of nonlinear dynamics of finding the best sparse fit to observational data in a large library of potential nonlinear models. We propose an efficient first-order Conditional Gradient algorithm for solving the underlying optimization problem. In comparison to the most prominent alternative framework, the new framework shows significantly improved performance on several essential issues like sparsity-induction, structure-preservation, noise robustness, and sample efficiency. We demonstrate these advantages on several dynamics from the field of synchronization, particle dynamics, and enzyme chemistry. •Identification of nonlinear dynamics from noidy data via sparse regression.•Enhanced sparsity improves robustness to noise, sample efficiency, and inference.•Conditional gradients based optimization promotes sparsity beyond l1 regularization.•Incorporating structure as linear (in)equality constraints is straightforward.